Barriers to Implementing Organic Waste-Based Fermented Feed Practices Among Livestock Farmers in Kuningan, West Java - Fakhrana Ghaisani Nazhira (Livestock Science & Innovation Journal, 2025)
Backround: Despite proven technical efficacy and economic benefits, organic waste-based fermented feed adoption remains persistently low among Indonesian livestock farmers, with commercial feed costs consuming 60-70% of production expenses while abundant organic wastes go unutilized, creating sustainability and profitability challenges.Objective: This study investigates barriers constraining fermented feed adoption among livestock micro-entrepreneurs.Method: A three-month qualitative study employed semi-structured interviews with 23 livestock farmers representing diverse adoption statuses (non-adopters, discontinued, sustained), complemented by observations and document review.Findings and Implications: Thematic analysis identified barrier categories and contextual adoption factors. Despite 95.7% awareness and 73.9% training attendance, only 21.7% achieved sustained adoption, with 30.4% having discontinued after attempting. Six interconnected barrier dimensions emerged: technical complexity (65.2% affected), knowledge deficits (60.9%), economic constraints (60.9%), time limitations (73.9%), psychological resistances (56.5%), and quality uncertainty (65.2%). Sustained adopters received intensive multi-session training with ongoing support, accessed reliable organic waste supplies, and benefited from active farmer group networks—factors largely absent for discontinued adopters and non-adopters. Villages with favorable institutional configurations achieved 40-50% adoption versus 0-5% elsewhere despite identical training.Conclusion: Effective promotion requires comprehensive interventions addressing multiple barriers simultaneously through participatory training, sustained implementation support, farmer organization strengthening, and organic waste supply chain facilitation rather than conventional one-time demonstrations, with institutional development as critical as farmer education for scaling sustainable livestock feeding practices.